Regulation of metal ions in smart metal-cluster nodes of metal-organic frameworks with open metal sites for improved photocatalytic CO2 reduction reaction - Dong, Hong; Zhang, Xin; Lu, Yang; Yang, Yan; Zhang, Yang-Peng; Tang, Hong-Liang; Zhang, Feng-Ming; Yang, Zhao-Di; Sun, Xiaojun; Feng, Yujie (Applied catalysis. B, Environmental, 2020)
We demonstrate that the regulation of metal species in metal-cluster nodes of PCN-250-Fe3 could realize a substantial improvement of conversion activity and selectivity of CO2 reduction. The photocatalysis results revealed that all bi-metallic PCN-250-Fe2M (M = Mn, Zn, Ni, Co) show better catalytic activity for stable reducing CO2 into CO compared with mono-metallic PCN-250-Fe3. [Display omitted] •We realized a substantial improvement of CO2 reduction activity by regulating the metal ions in metal-cluster nodes of MOFs.•PCN-250-Fe2Mn shows the maximum photocatalytic activity of 21.51 mmol h−1 g−1.•PCN-250-Fe2Mn is the best performance MOF-based photocatalyst for CO2 reduction on the similar reaction condition until now.•Introducing the second MII could promote the migration of photogenerated electrons to active sites Metal-organic frameworks (MOFs) have exhibited promising potential in the field of photocatalysis CO2 conversion, while improving the conversion activity of CO2 by regulating the metal species in the metal-cluster nodes of MOFs has not been systematically explored. Herein, we realized a substantial improvement of CO2 conversion activity by regulating the metal species in metal-cluster nodes of MOFs and obtain the best performance MOF photocatalysts for CO2 conversion. A stable MOF, PCN-250-Fe3 with Fe2IIIFeII metal-cluster nodes and open metal sites was synthesized, and we further improve its CO2 reduction activity by tuning the species of MII metal ions in the cluster. The photocatalytic results revealed that all bi-metallic PCN-250-Fe2M (M = Mn, Zn, Ni, Co) show better catalytic activity and selectivity for stable reducing CO2 into CO, compared with mono-metallic PCN-250-Fe3. Especially, PCN-250-Fe2Mn shows the maximum photocatalytic activity of 21.51 mmol h−1 g−1 under visible light irradiation, which is the best performance MOF-based photocatalyst for CO2 conversion on the similar reaction condition until now. Further investigations and theoretical calculations reveal that the introduction of the second MII metal ions could promote the migration of photogenerated electrons to active sites and improve the CO2 adsorption and activation by favoring the CO2 reduction rout and restraining the production of hydrogen evolution intermediate.